2021
DOI: 10.3390/ma14206010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Surface Roughness in Milling of DuralcanTM Composite

Abstract: In today’s developing aircraft and automotive industry, extremely durable and wear-resistant materials, especially in high temperatures, are applied. Due to this practical approach, conventional materials have been superseded by composite materials. In recent years, the application of metal matrix composites has become evident in industry 4.0. A study has been performed to analyze the surface roughness of aluminum matrix composites named Duralcan® during end milling. Two roughness surface parameters have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[Duralcan™ is an aluminum matrix supplemented with ceramic particles like alumina and silicon carbide. The study reported in [114] adjusted milling settings to obtain the required surface roughness characteristics.…”
Section: Aluminium Reinforced With Silicon (Al/si)mentioning
confidence: 99%
“…[Duralcan™ is an aluminum matrix supplemented with ceramic particles like alumina and silicon carbide. The study reported in [114] adjusted milling settings to obtain the required surface roughness characteristics.…”
Section: Aluminium Reinforced With Silicon (Al/si)mentioning
confidence: 99%
“…1 (2024) [14][15][16][17][18][19][20] the subject of an experimental study. Wiciak-Pikuła et al [13] For milling DuralcanTM Composite, a model based on an artificial neural network (ANN) based vibration and a model based on experimental design were established to analyze the effects of machining parameters such as cutting speed, spindle speed, and feed rate, axial infeed depth, and radial infeed depth. Layatitdev Das et al [14] Input machining parameters (cutting speed, tool feed, and cutting depth) and their effects on machining forces, MRR, and surface roughness during milling are studied in the creation of Ti6Al4V metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Although these technologies were described in many articles [22][23][24][25][33][34][35][36][37][38][39][40], this study combines the bene ts of these both methods. Numerous research centers make attempts on using LAM for machining metal matrix composites [41,42], ceramics [41,43], titanium [40] and nickel alloys [34,36], however, there were no attempts for using LAM for laser alloyed surfaces. The results obtained in this study allow to evaluate effects of this treatment.…”
Section: Introductionmentioning
confidence: 99%